Unraveling mitochondrial crosstalk: a new frontier in heart failure pathogenesis - Chang, Hongbo; He, Pingge; Liu, Weidi; Wu, Hong; Wang, Zhentao (Frontiers in Cardiovascular Medicine, 2025)
Mitochondria play a central role in energy production and signal transduction in cardiomyocytes. Their dysfunction is a key contributor to the development and progression of heart failure (HF). Beyond energy metabolism, mitochondria regulate calcium homeostasis, autophagy, protein synthesis, lipid metabolism, and gene expression through close interactions with other organelles. Disruption of these interactions has been linked to HF pathophysiology.This review focuses on the dynamic communication between mitochondria and five major organelles—the endoplasmic reticulum, lysosomes, ribosomes, lipid droplets, and the nucleus. We outline how these interactions maintain cardiac homeostasis and describe how their dysfunction contributes to HF. We also highlight emerging therapeutic strategies targeting these organelle networks.